Impact of Cultural Dimensions of Multicultural Project Teams - Fielder search in the Diyala bridge area project - الفيحان ايثار عبد الهادي; حسن مصطفى حسين (Journal of Economics and Administrative Sciences, 2014)
This search that addressed with (( The Impact of Cultural Dimensions in multicultural Project Teams )) tagged is important variables in the project environment that rare has been adverted in Arabic studies . The search problem is reflected in missing of awareness towards a cultural dimensions of the Diyala bridge area project team and their impact in project communications ، as well as weak project management interest in adopting a clear and scientific approach in the management and organization of project communications in order to reach the objective of the study ، was used questionnaire that built depending on previous global studies and has been adapted to accommodate Iraqi business environment ، And have been applied in (the Diyala bridge area streams project) In order to interpret the results and hypotheses of the search using a set of statistical tools، including the arithmetic mean، standard deviation and coefficient of variation for the diagnosis and interpretation of the answers of questionnaire respondents، and using correlation coefficient Spearman to know the nature of the relationship between variables ، besides coefficient of simple linear regression and multiple to determine the effect of the interpretation variable the cultural dimensions in the responder variable the communications. There is a correlation relationship and morale effects of the cultural dimensions that have the project team at project team communication ،therefore Increase of the managers understanding and awareness of the dimensions and try employ them effectively for increase cooperation and interaction between the various individuals in the project .